2014
DOI: 10.2147/ahmt.s48053
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in the treatment of adolescent drug use

Abstract: Research on the development and efficacy of drug abuse treatment for adolescents has made great strides recently. Several distinct models have been studied, and these approaches range from brief interventions to intensive treatments. This paper has three primary aims: to provide an overview of conceptual issues relevant to treating adolescents suspected of drug-related problems, including an overview of factors believed to contribute to a substance use disorder, to review the empirical treatment outcome litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 54 publications
1
56
0
4
Order By: Relevance
“…Consistent with previous findings with these interventions, the parent component in BI-AP was associated with an increase in effectiveness of the BI for all youth, including those with marijuana dependence, conduct problems, or symptoms of depression or anxiety, when compared to the youth-only, BI-A intervention (Winters et al, 2012). This result is in line with the general large drug abuse treatment literature showing relatively better outcomes when parents are involved in the therapy compared to therapy involving only the adolescent (see Tanner-Smith, Wilson, & Lipsey, 2013; Winters, Tanner-Smith, Bresani, & Myers, 2014). …”
Section: Discussionsupporting
confidence: 84%
“…Consistent with previous findings with these interventions, the parent component in BI-AP was associated with an increase in effectiveness of the BI for all youth, including those with marijuana dependence, conduct problems, or symptoms of depression or anxiety, when compared to the youth-only, BI-A intervention (Winters et al, 2012). This result is in line with the general large drug abuse treatment literature showing relatively better outcomes when parents are involved in the therapy compared to therapy involving only the adolescent (see Tanner-Smith, Wilson, & Lipsey, 2013; Winters, Tanner-Smith, Bresani, & Myers, 2014). …”
Section: Discussionsupporting
confidence: 84%
“…Saules et al (2010) found that, among 54 bariatric patients (mean age= 44.6 ±9.1) who were enrolled in a drug and alcohol treatment program, 35.8% of them had a preoperative history of heavy use of drugs and/or alcohol. With regards to relatively high prevalence rates for alcohol, marijuana, amphetamines and tobacco use among adolescents (Winters et al, 2014; Carneiro et al, 2006), bariatric surgery patients at younger age were more likely to present substance use problems than those at older age (King et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Although adolescence is a key developmental stage for substance use progression, the current profile of intervention options for adolescents who misuse substances is limited in scope, due to an almost exclusive reliance on psychosocial treatments with limited effectiveness (17). The state of the science on outpatient psychosocial interventions for adolescent substance misuse, especially at lower levels of use, is trending toward brief, person-centered approaches that provide individually tailored information to youth across a variety of settings (18).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, compelling evidence from several branches of medicine demonstrate that the safety and efficacy of medication use with adolescents cannot be inferred from adult data (28-30), and this concern may be especially important in the substance abuse field (31). There is strong evidence that teenagers differ considerably from adults in terms of their symptom presentation, course, and associated features of SUDs, and these differences appear to be driven in part by substantial neuronal remodeling that occurs during adolescence (17, 32, 33). These changes impact adolescents’ sensitivity to alcohol and possibly other drugs, heighten their vulnerability to heavy drinking, other drug use, and the development of substance use problems, and possibly impact how they respond to medications (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation